Tindak Pidana Pencemaran Nama Baik Oleh Anak Di Bawah Umur Dengan Menggunakan Media Sosisal Elektronik - Oktavina, Margaretha Andini; Firmansyah, Hery (UNES Law Review, 2023)
The criminal act of defamation by minors via electronic social media is an important issue in criminal law. This research aims to determine the threat of punishment for criminal acts of defamation using electronic social media and criminal liability for minors who commit ITE criminal offenses. The research method used is the normative juridical method. The results of the research show that there is a threat of strict sanctions against perpetrators of criminal acts of defamation using electronic social media, where the perpetrator can be punished with a maximum imprisonment of 4 years and/or a maximum fine of IDR 750,000,000.00. Criminal liability for minors who commit criminal acts of defamation through social media can be implemented by paying attention to the special provisions regarding children's rights in Law Number 11 of 2021 concerning the Juvenile Justice System. This responsibility is imposed in accordance with the criminal elements which have been reviewed from the terms of criminal liability, so that perpetrators of criminal acts of defamation through social media can be held accountable for their actions as decided in court. Thus, the protection of children's rights and the application of criminal sanctions need to be harmonized with applicable legal provisions and pay attention to the special implementation of children's rights in the juvenile justice system.